Fracture properties of nanographene reinforced EPON 862 thermoset polymer system. (19th June 2015) - Kumar, Abhishek; Li, Shibo; Roy, Samit; King, Julia A.; Odegard, Greg M.
Abstract: This paper studies the differences in fracture properties (stress intensity factors and energy release rates) of nanocomposites of thermosetting polymer EPON 862 and its nano-graphene reinforced counterparts. Extremely low (0.1 and 0.5) weight percent nano-graphene platelets were dispersed in EPON 862 matrix and compact tension (CT) fracture experiments were conducted under quasi static loading conditions using displacement control. Significant enhancements in fracture toughness (∼200%), and energy release rate (∼570%) respectively were observed for nano-graphene reinforced matrix for only 0.5 wt% of graphene platelets. Fractography analysis of the fractured CT specimens was used to qualitatively visualize and understand the mechanism(s) responsible for the enhancement in these properties using Scanning Electron Microscopy (SEM). Evidence of crack deflection due to increased surface roughness, graphene platelet pullout and plastic deformation of the matrix causing filler-matrix debonding, was observed from SEM micrographs, caused by the addition of nano-graphene platelets (NGP). Atomic Force Microscopy (AFM) was also used to quantify the magnitude of surface roughness changes between the NGP reinforced and reinforced nano-composite samples, and correlate surface roughness changes due to crack deflection to increased fracture toughness.